STUDI KOMPARASI HUKUM TERHADAP ABORSI DENGAN INDIKASI CACAT JANIN (Fatwa MUI No. 04 Tahun 2005 dan Undang – Undang No. 36 Tahun 2009 Tentang Kesehatan) - Riza Shihabudin Pradana; Masrokhin Masrokhin (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This research aims to compare abortion laws for indications of fetal defects according to Islamic law and Law no. 36 of 2009. This research uses library research to examine the comparison of Islamic law and Law no. 36 of 2009 concerning abortion due to fetal defects. Data was taken from primary and secondary sources, then analyzed using descriptive analysis and content analysis methods to compile research findings. The research results show that the majority of Islamic scholars agree that abortion after 120 days of pregnancy is haram except in emergencies, with some schools of thought such as the Hanafi allowing abortion before 120 days under certain conditions. Law Number 36 of 2009 concerning Health in Indonesia also prohibits abortion except to save the mother's life, avoid the birth of a baby with severe genetic defects, or as a result of rape, and must be carried out by competent health personnel after going through counseling. Islamic Law and Law no. 36 of 2009 has a similar view that abortion is not permitted except in emergency situations to protect the life of the mother or fetus, with differences regarding gestational age affecting its permissibility.